2022
DOI: 10.3389/fneur.2022.912728
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Spectroscopy May Help Diagnose Sporadic Meningioangiomatosis Associated With Meningioma: A Case Report

Abstract: Herein, we have presented the clinical features of meningioangiomatosis associated with meningioma, which is considered to be a rare neoplastic lesion. Magnetic resonance spectroscopy (MRS) demonstrated a remarkably decreased N-acetylaspartate peak and an increase in the choline peak of the lesion, suggesting neuronal injury and active cell proliferation. These findings substantially differed from those observed in the case of pure meningioangiomatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Radiologically, pre-surgical diagnosis of MA-M is challenging due to its variable appearances. MRI is usually the imaging modality of choice, and MA-M lesions typically appear hypo-or iso-intense on T1-weighted images and hyperintense on T2-weighted images ( 24 ). MRI results showed that the majority of the MA-M cases had intracortical non-enhanced lesions without dural attachment.…”
Section: Discussionmentioning
confidence: 99%
“…Radiologically, pre-surgical diagnosis of MA-M is challenging due to its variable appearances. MRI is usually the imaging modality of choice, and MA-M lesions typically appear hypo-or iso-intense on T1-weighted images and hyperintense on T2-weighted images ( 24 ). MRI results showed that the majority of the MA-M cases had intracortical non-enhanced lesions without dural attachment.…”
Section: Discussionmentioning
confidence: 99%